Enhanced mechanical properties of the nanostructured AlN-graphene composites rapidly sintered by high-frequency induction heating. Issue 14 (1st November 2016) - Shon, In-Jin
Abstract: Despite of many attractive properties of AlN, the current concern about the AlN focuses on its low fracture toughness below the ductile-brittle transition temperature. To improve its mechanical properties, the approach commonly utilized has been the addition of a second phase to form composites and to make nanostructured materials. In this respect, graphene was evaluated as the reinforcing agent of AlN ceramics using novel sintering method (high-frequency induction heated sintering method). Highly dense nanostructured AlN and AlN-graphene composites were achieved within two min at 1600 °C. The effect of graphene on the microstructures and the mechanical properties (hardness and fracture toughness) of AlN-graphene composites was investigated using FE-SEM and Vickers hardness tester.